Acid-resistant nano polymer microsphere inclusion plugging system as well as preparation method and application thereof
Through the inclusion cooperation between acid-resistant nanopolymer microspheres and cyclodextrin polymers, a sealing system with strong acid resistance and excellent shear resistance is constructed, and the poor acid resistance and suspension of nanopolymer microspheres in the prior art are solved. The problem of weak stability improves CO2 displacement efficiency and recovery rate.
Patent Information
- Application Number
- CN202410935700.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-07-12
AI Technical Summary
The existing nanopolymer microspheres have poor acid resistance and weak suspension stability in low-permeability reservoirs, resulting in poor CO2 gas-fighting and sealing effect, affecting the oil field gas injection development effect.
Acid-resistant nanopolymer microspheres and cyclodextrin polymers are used to construct an inclusion and efficiency sealing system through the host-guest inclusion cooperation to improve the acid resistance and shear resistance of microspheres and enhance their dispersion under acidic conditions. and blocking capability.
A nanopolymer microsphere inclusion and sealing system with strong acid resistance and excellent shear resistance is realized, which can effectively enter the deep strata, improve CO2 displacement efficiency and recovery rate, and solve the problem of gas trapping and sealing.
Smart Images

Figure BDA0004941255660000031 
Figure BDA0004941255660000032 
Figure BDA0004941255660000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and natural gas development, and specifically relates to an acid-resistant nano polymer microsphere inclusion plugging system and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] At present, low permeability reservoirs are an important area for increasing reserves and production in my country. 2 The flooding technology solves the problem of "no injection and no production" in low permeability reservoir water injection development, effectively improving the utilization rate and recovery rate of crude oil in low permeability reservoirs; however, due to the existence of fractures and high permeability channels in low permeability reservoirs, gas channeling is prone to occur during the development of such reservoirs, which seriously affects the effect of gas injection development in oil fields. 2 The plugging technology of flooding has far-reaching significance for the efficient development of low permeability oil and gas reservoirs.
[0004] For CO 2 To solve the problem of gas channeling, the development of acid-resistant gas channeling plugging materials is the key. Polymer microspheres have shown great development prospects in low permeability reservoir channeling plugging. They can migrate in cracks or microcracks to the deep reservoir to achieve deep plugging. However, the commonly used nano-polymer microspheres have poor acid resistance and limited effect of particle plugging gas. Nano-polymer microspheres are often compounded with polymer solutions during application. The high viscosity of the polymer enhances the suspension and dispersion stability of the nano-polymer microspheres and carries them into the injection well. The commonly used polymer is partially hydrolyzed polyacrylamide. The interaction strength between the polymer and the nano-polymer microspheres is low, and the polymer is not easily oxidized in supercritical CO. 2 The viscosity increasing ability under acidic conditions is limited, so the composite system has limited synergistic plugging effect in application. For this reason, the present invention is proposed. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides an acid-resistant nano-polymer microsphere inclusion plugging system and its preparation method and application. The present invention introduces the supramolecular construction concept, and proposes an acid-resistant nano-polymer microsphere and a cyclodextrin polymer through the host-guest inclusion reaction to construct an inclusion enhancement plugging system, which solves the problems of poor deformability, weak suspension stability, poor expansion performance under acidic conditions, poor acid resistance, and limited gas plugging effect of particles of conventional polymer microspheres. The plugging system of the present invention has strong acid resistance and excellent shear resistance, wherein the nano-polymer microspheres have good dispersibility, good injectability, and are easy to be injected into the formation and migrate to deep; at the same time, they have the characteristics of low concentration and high efficiency, can effectively enter the deep formation and efficiently plug the cracks, thereby improving CO 2 The swept volume and displacement efficiency.
[0006] The present invention is achieved through the following technical solutions:
[0007] An acid-resistant nano polymer microsphere inclusion plugging system is prepared by comprising the following raw materials in parts by weight: 1-5 parts of acid-resistant nano polymer microspheres, 1-5 parts of acid-resistant low molecular weight cyclodextrin polymers, and 80-120 parts of water.
[0008] Preferably, according to the present invention, the acid-resistant nano polymer microsphere inclusion plugging system is prepared by including the following raw materials in parts by weight: 2-4 parts of acid-resistant nano polymer microspheres, 2-4 parts of acid-resistant low molecular weight cyclodextrin polymer, and 90-110 parts of water.
[0009] Preferably, the acid-resistant nano polymer microsphere inclusion plugging system is prepared by including the following raw materials in parts by weight: 3 parts of acid-resistant nano polymer microspheres, 3 parts of acid-resistant low molecular weight cyclodextrin polymer, and 100 parts of water.
[0010] Preferably, according to the present invention, the acid-resistant nano-polymer microspheres are prepared by including the following raw materials in parts by weight: 110-150 parts of basic building block monomers, 1-15 parts of hydrophobic monomers, 1-20 parts of acid-resistant monomers, 0.1-3 parts of nanoparticles, 0.3-6 parts of double cross-linking agent systems, 0.2-3 parts of initiators, 150-200 parts of emulsifiers, 500-550 parts of oil phase solvents, and 100-200 parts of water.
[0011] Preferably, the acid-resistant nano polymer microspheres are prepared by including the following raw materials in parts by weight: 130-140 parts of basic building block monomers, 2-4 parts of hydrophobic monomers, 1-2 parts of acid-resistant monomers, 0.4-0.6 parts of nanoparticles, 3-5 parts of double cross-linking agent systems, 0.8-1.2 parts of initiators, 180-185 parts of emulsifiers, 510-520 parts of oil phase solvents, and 155-160 parts of water.
[0012] Preferably, the acid-resistant nano-polymer microspheres are prepared by including the following raw materials in parts by weight: 132 parts of basic building block monomers, 3 parts of hydrophobic monomers, 1 part of acid-resistant monomers, 0.5 parts of nanoparticles, 4 parts of double cross-linking agent system, 1.125 parts of initiator, 181.2 parts of emulsifier, 518.8 parts of oil phase solvent, and 158.5 parts of water.
[0013] Preferably, the basic building block monomer is acrylamide (AM).
[0014] Preferably, the hydrophobic monomer is hexadecyl dimethyl allyl ammonium chloride.
[0015] Preferably, the acid-resistant monomer is diallyldimethylammonium chloride.
[0016] Preferably, the nanoparticles are modified nano-silicon dioxide (SiO 2 ), modified nano-silicon dioxide (SiO 2 ) has the structure shown below, and the particle size is 1-10 nm. The preparation method of modified nano silicon dioxide with carbon-carbon double bonds on the surface can be prepared according to the existing technology.
[0017]
[0018] Preferably, the dual crosslinker system is a combination of a stable crosslinker N,N-methylenebisacrylamide and an unstable crosslinker polyethylene glycol diacrylate, wherein the mass ratio of N,N-methylenebisacrylamide to polyethylene glycol diacrylate is 6:4-9:1, preferably 2:1-4:1.
[0019] Preferably, the initiator is 2,2'-azo(2-methylpropylamidine) dihydrochloride.
[0020] Preferably, the emulsifier is a combination of sorbitan fatty acid ester and polyoxyethylene sorbitan monooleate, wherein the mass ratio of sorbitan fatty acid ester to polyoxyethylene sorbitan monooleate is 2-3:1.
[0021] Preferably, the oil phase solvent is white oil.
[0022] According to the present invention, the particle size of the acid-resistant nano polymer microspheres is preferably 150-300 nm. Preferably, the particle size of the acid-resistant nano polymer microspheres is 150-200 nm.
[0023] According to the present invention, the acid-resistant nano polymer microspheres have the following structure:
[0024]
[0025] According to a preferred embodiment of the present invention, a method for preparing acid-resistant nano-polymer microspheres comprises the steps of:
[0026] (1) fully dispersing the basic building block monomer, the hydrophobic monomer, the acid-resistant monomer, the nanoparticles, and the dual crosslinking agent system in water to obtain an aqueous phase;
[0027] (2) dissolving an emulsifier in an oil phase solvent to obtain an oil phase;
[0028] (3) mixing the aqueous phase and the oil phase and emulsifying them to obtain a microemulsion;
[0029] (4) adding an initiator aqueous solution to the microemulsion, reacting, breaking the emulsion by phase transition, filtering, washing, drying, grinding, granulating, and sieving to obtain acid-resistant nano-polymer microspheres.
[0030] Preferably, in step (3), the aqueous phase is added dropwise to the oil phase at a rate of 1-2 drops per second at room temperature and under stirring conditions of 500-700 r / min.
[0031] Preferably, in step (3), the emulsification speed is 500-700 r / min, and the emulsification time is 20-40 min.
[0032] Preferably, in step (4), the mass concentration of the initiator aqueous solution is 1%-5%; the dropping rate is 1-2 drops per second; the dropping temperature is 35-50°C; the dropping is carried out under stirring at 300-400r / min and protective gas protection conditions. Preferably, the protective gas is nitrogen or argon.
[0033] Preferably, in step (4), the reaction temperature is 35-50°C, the reaction time is 3-6 hours, and the reaction is carried out at a stirring rate of 300-400 r / min under the protection of a protective gas. Preferably, the protective gas is nitrogen or argon.
[0034] Preferably according to the present invention, the acid-resistant low molecular weight cyclodextrin polymer is prepared by including the following raw materials in parts by weight: 60-80 parts of basic building unit monomer a, 1-10 parts of inclusion monomer, 1-5 parts of acid-resistant monomer a, 1-10 parts of temperature-resistant monomer a, 1-10 parts of raft chain transfer agent, 2-4 parts of initiator system, and 100-200 parts of water.
[0035] Preferably, the acid-resistant low molecular weight cyclodextrin polymer is prepared by the following raw materials in parts by weight: 70-80 parts of basic building unit monomer a, 3-5 parts of inclusion monomer, 1-2 parts of acid-resistant monomer a, 7-9 parts of temperature-resistant monomer a, 5-7 parts of raft chain transfer agent, 1-3 parts of initiator system, and 140-160 parts of water.
[0036] Further preferably, the acid-resistant low molecular weight cyclodextrin polymer is prepared by the following raw materials in parts by weight: 75 parts of basic building unit monomer a, 4 parts of inclusion monomer, 1 part of acid-resistant monomer a, 8 parts of temperature-resistant monomer a, 6 parts of raft chain transfer agent, 2 parts of initiator system, and 150 parts of water.
[0037] Preferably, the basic building block monomer a is a combination of acrylamide (AM) and acrylic acid (AA), wherein the mass ratio of acrylamide (AM) to acrylic acid (AA) is 8:1-10:1.
[0038] Preferably, the inclusion monomer is allyl β-cyclodextrin.
[0039] Preferably, the acid-resistant monomer a is diallyldimethylammonium chloride.
[0040] Preferably, the temperature-resistant monomer a is sodium 3-(N-allyl-N-methylamino)propane-1-sulfonate.
[0041] Preferably, the raft chain transfer agent is benzyl dithiobenzoate.
[0042] Preferably, the initiator system is a three-stage initiator or a photoinitiator. Further preferably, the three-stage initiator system is a combination of a low-temperature initiator, a medium-temperature initiator and a high-temperature initiator; the low-temperature initiator is potassium persulfate and sodium bisulfite, and the mass ratio of potassium persulfate to sodium bisulfite is 1:1; the medium-temperature initiator is 2,2'-azo (2-methylpropyl amidine) dihydrochloride; the high-temperature initiator is cyclohexanone peroxide; the mass ratio of the low-temperature initiator, the medium-temperature initiator and the high-temperature initiator is 1:1:1. The photoinitiator is a water-soluble photoinitiator 2,2'-azo (2-methylpropyl amidine) dihydrochloride.
[0043] According to the present invention, the acid-resistant low molecular weight cyclodextrin polymer has the structure shown below:
[0044]
[0045] According to a preferred embodiment of the present invention, a method for preparing an acid-resistant low molecular weight cyclodextrin polymer comprises the steps of:
[0046] The basic building unit monomer a, inclusion monomer, acid-resistant monomer a, heat-resistant monomer a and raft chain transfer agent are fully dispersed in water, and the pH of the system is adjusted to 7; an initiator system is added dropwise, reacted, and then washed, crushed, dried and granulated to obtain an acid-resistant low molecular weight cyclodextrin polymer.
[0047] Preferably, a NaOH aqueous solution with a mass concentration of 10-30% is used to adjust the pH of the system.
[0048] Preferably, when the initiator system is a three-stage initiator, the initiator system is an aqueous solution of the three-stage initiator with a mass concentration of 2%-5%; the reaction conditions are as follows: stirring at 3-8°C under protective gas protection until the system becomes viscous, and then standing at 3-8°C under protective gas protection for 1-10 hours. More preferably, the protective gas is nitrogen or argon.
[0049] Preferably, when the initiator system is a photoinitiator, the reaction is carried out under ultraviolet light irradiation and protective gas protection, the reaction temperature is room temperature, and the reaction time is 2-4 hours; further preferably, the protective gas is nitrogen or argon; the ultraviolet light is provided by an ultraviolet high-pressure mercury lamp.
[0050] The preparation method of the acid-resistant nano polymer microsphere inclusion plugging system comprises the following steps:
[0051] The acid-resistant nano polymer microspheres are fully dispersed in water, expanded and aged to obtain a microsphere dispersion; an acid-resistant low molecular weight cyclodextrin polymer is added, fully dispersed, and then aged to obtain an acid-resistant nano polymer microsphere inclusion plugging system.
[0052] Preferably according to the present invention, the expansion reaction temperature is 40-50° C., the expansion reaction time is 2-6 hours, and the expansion reaction is carried out under stirring conditions of 50-200 r / min.
[0053] Preferably according to the present invention, during the preparation of the microsphere dispersion, the aging reaction temperature is 40-50° C., and the aging reaction time is 20-30 h.
[0054] Preferably according to the present invention, after adding the acid-resistant low molecular weight cyclodextrin polymer, stirring is carried out at 40-50° C. and 50-200 r / min for 2-6 hours to fully disperse it.
[0055] Preferably according to the present invention, after adding the acid-resistant low molecular weight cyclodextrin polymer, the aging reaction temperature is 40-50° C., and the aging reaction time is 30-70 hours.
[0056] The application of the above acid-resistant nano polymer microsphere inclusion plugging system is applied to CO 2 Plug gas channel in oil reservoir.
[0057] The technical features and beneficial effects of the present invention are as follows:
[0058] 1. The acid-resistant nano polymer microsphere inclusion plugging system provided by the present invention is environmentally friendly, has a wide source of raw materials and is low in cost.
[0059] 2. The acid-resistant nano polymer microspheres involved in the present invention have a double cross-linking effect in their molecular structure. The stable cross-linking agent N,N-methylenebisacrylamide and the unstable cross-linking agent polyethylene glycol diacrylate constitute the double cross-linking effect of the polymer microspheres. Polyethylene glycol diacrylate contains ester bonds and is a temperature-sensitive monomer; when the polymer microspheres are in a temperature environment higher than 60°C, the ester bonds in the unstable cross-linking agent will break. Therefore, the double cross-linking structure of the present invention has three effects: first, the polymer microspheres have good injectability; due to the double cross-linking effect, the polymer microspheres are in places with lower temperatures such as ground equipment, wellbores, and near injection wells. The unstable cross-linking agent can play a cross-linking role, so that the polymer microspheres have a denser cross-linking structure. At this time, the polymer microspheres have poor water absorption and expansion, small particle size, delayed expansion characteristics, and are easy to be injected into the formation and migrate to deep. Second, the polymer microspheres have strong deep plugging properties; due to the delayed expansion caused by the double cross-linking effect, the polymer microspheres enter the deep formation, and after reaching the high-temperature area, the ester bonds in the unstable cross-linking agent break, and the polymer microspheres can absorb water and expand for the second time, thereby achieving effective plugging in the deep formation. Third, the acid resistance of the polymer microspheres is improved; the presence of cationic acid-resistant monomer diallyldimethylammonium chloride in the molecular structure of acid-resistant nano polymer microspheres can keep the polymer microsphere molecular chain in an extended configuration in an acidic environment, and can be acid-resistant; and the secondary expansion characteristics of the microspheres caused by the unstable cross-linking agent can give the polymer microspheres another level of acid resistance to a certain extent.
[0060] 3. Since the hydrophobic monomer hexadecyl dimethyl allyl ammonium chloride is introduced into the acid-resistant nano polymer microspheres of the present invention during the synthesis process, the hydrophobic monomer in the microspheres after the reaction presents three states: ① both ends of the hydrophobic chain and the main chain are all inside the microspheres; ② both ends of the hydrophobic chain are inside the microspheres, and the main chain is outside the microspheres; ③ one end of the hydrophobic chain is inside the microspheres, and the other end is outside the microspheres. Only the microspheres formed by ③ can undergo supramolecular inclusion complexation with the β-cyclodextrin cavity to form a composite system. Figure 1 (a) is an acid-resistant nanopolymer microsphere with one end of the hydrophobic chain inside the microsphere and the other end outside the microsphere.
[0061] 4. The acid-resistant low molecular weight cyclodextrin polymer involved in the present invention has a controllable molecular weight, strong shear resistance, good high temperature resistance and acid resistance. The RAFT chain transfer agent used in the present invention can allow the β-cyclodextrin monomer block to enter the polymer molecular chain, so that the controllable preparation of the polymer can be achieved. The RAFT polymerization technology involved in the present invention can make the polymer molecular weight controllable, so the prepared cyclodextrin polymer has a low molecular weight (below 1 million), and can have an excellent viscosity-increasing effect at a low molecular weight. The low molecular weight cyclodextrin polymer prepared by the present invention has good shear resistance under high-speed shear due to the inclusion synergistic effect of β-cyclodextrin. The acid-resistant low molecular weight cyclodextrin polymer of the present invention is as follows Figure 1 (b), it is mainly divided into two parts, a hydrophilic main chain composed of acrylamide / acrylic acid and a side chain containing the β-cyclodextrin cavity. Cyclodextrin is a general term for a series of cyclic oligosaccharides connected by α-1,4 glycosidic bonds generated by amylose under the action of cyclodextrin glucosyltransferase (fermented by Bacillus). Usually, each cyclodextrin molecule contains 6 to 12 pyranose glucose units. The number of glucose units is different and the spatial size is also different. Among them, the most studied are α-CD, β-CD and γ-CD with 6, 7 and 8 glucose units respectively. There are a large number of hydrophobic groups inside the ring cavity due to the shielding effect of the CH bond, which makes the cavity present a strong hydrophobic property. Therefore, when in a certain solvent environment, on the one hand, the hydrophobicity of the cyclodextrin cavity allows it to form a host-guest inclusion complex with a certain stable structure with a small guest molecule that matches its space.
[0062] 5. The acid-resistant nano polymer microsphere inclusion plugging system of the present invention has the characteristics of low concentration and high efficiency, that is, high viscosity and excellent plugging effect can be achieved at a relatively low concentration. The acid-resistant nano polymer microspheres of the present invention have a hydrophobic alkyl long chain guest structure in their molecular structure, and a β-cyclodextrin main structure in the acid-resistant low molecular weight cyclodextrin polymer molecular chain; the hydrophobic alkyl long chain guest structure and the β-cyclodextrin main structure have an inclusion-enhanced supramolecular interaction, which can achieve the purpose of low concentration and high efficiency between the polymer microspheres and the polymer, such as Figure 1 (c) As shown. On the one hand, the inclusion complex between the polymer microspheres and the polymer enhances the network structure of the polymer itself and can enhance the viscosity of the polymer; on the other hand, the polymer has a high viscosity, which can keep the polymer microspheres well dispersed in the dispersed system without aggregation, which is beneficial to the migration of the polymer microspheres under the action of formation seepage.
[0063] 6. The acid-resistant nano polymer microsphere inclusion plugging system of the present invention has strong acid resistance, excellent shear resistance, good injectability, and is easy to be injected into the formation and migrate to the deep part; at the same time, it has the characteristics of low concentration and high efficiency, and can effectively enter the deep formation and efficiently plug the cracks, thereby improving CO 2 The swept volume and displacement efficiency.
[0064] 7. The acid-resistant monomer in the raw material composition of the acid-resistant nano polymer microspheres involved in the present invention and the double cross-linked structure in the molecular structure design are extremely important. The strong acid resistance and high plugging effect of the acid-resistant nano polymer microspheres are mainly achieved by these two aspects. The acid-resistant monomer is diallyldimethylammonium chloride, and there are polymerizable C=C double bonds at both ends of the molecular structure, which participate in the molecular structure through cyclization during the reaction; its five-membered ring structure and positive charge properties make it highly acid-resistant; on the other hand, the double cross-linked structure makes the acid-resistant nano polymer microspheres have temperature-sensitive properties, and secondary expansion can be achieved to enhance acid resistance under harsh reservoir conditions.
[0065] 8. The inclusion monomer allyl β-cyclodextrin and the temperature-resistant monomer 3-(N-allyl-N-methylamino) propane-1-sulfonate sodium in the raw material composition of the acid-resistant low molecular weight cyclodextrin polymer involved in the present invention are extremely important. Among them, there are acid-resistant monomers in the cyclodextrin polymer that are consistent with the acid-resistant effect of the acid-resistant nano-polymer microspheres. Therefore, in terms of improving the performance of the polymer, the inclusion monomer and the temperature-resistant monomer are more important. Allyl β-cyclodextrin is the structural basis for ensuring the inclusion supramolecular effect between the polymer and the polymer microspheres. Sodium 3-(N-allyl-N-methylamino)propane-1-sulfonate has a sulfonic acid group, so it plays an important role in temperature resistance. Under acidic conditions, the tertiary amine group in sodium 3-(N-allyl-N-methylamino)propane-1-sulfonate is protonated to become an ammonium group, which makes the monomer become a zwitterionic structure under acidic conditions. The hydrogen ions form a double-layer structure of counterions near the sulfonic acid group. The ammonium group has the same effect as the ammonium group in the acid-resistant monomer, which can make the polymer achieve stronger acid resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 It is a schematic diagram of the structure of the acid-resistant nano-polymer microsphere (a), the acid-resistant low molecular weight cyclodextrin polymer (b) and the acid-resistant nano-polymer microsphere inclusion plugging system (c). DETAILED DESCRIPTION
[0067] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0068] Preparation method of modified nano-silica with carbon-carbon double bonds on the surface. Reference DOI number: https: / / doi.org / 10.1016 / j.colsurfa.2018.03.034. The specific preparation steps are as follows: weigh 1g of nano-silica and disperse it in a mixed solution of 44mL of deionized water and anhydrous ethanol for 1 hour by ultrasonic. The volume ratio of deionized water to ethanol is 1:10. After dispersion, place it in a three-necked flask, connect the nitrogen port, condenser reflux tube and stirring device, set the constant water bath temperature to 50°C and the stirring rate to 500r / min. Add 1.03g of silane coupling agent 3-(isobutylene acyloxy)propyltrimethoxysilane and 10 drops of ammonia water with a mass concentration of 28% to the dispersion of nano-silica. After reacting for 24 hours, centrifuge the solution and precipitate it. The product is rinsed with anhydrous ethanol 3-5 times and then dried to obtain modified nano-silica with carbon-carbon double bonds on the surface. The particle size is between 1-10nm.
[0069] The polyethylene glycol diacrylate used in the examples has an average molecular weight of 308 and is commercially available.
[0070] Example 1
[0071] A method for preparing an acid-resistant nano polymer microsphere inclusion plugging system comprises the following steps:
[0072] (1) Preparation of acid-resistant nanopolymer microspheres:
[0073] Preparation method: accurately weigh 0.1g of diallyldimethylammonium chloride and 0.3g of N,N-methylenebisacrylamide and dissolve them in 15.85g of deionized water, and stir them evenly with a magnetic stirrer; weigh 13.2g of acrylamide, 0.1g of polyethylene glycol diacrylate, and 0.3g of hexadecyldimethylallylammonium chloride and dissolve them in the above solution; after each agent is completely dissolved, continue stirring for 5 minutes before dissolving other agents, and finally weigh 0.05g of modified nano-silica with carbon-carbon double bonds on the surface and disperse it evenly by ultrasonication; after all agents are evenly dissolved, pass nitrogen for 10 minutes and ultrasonically oscillate for 10 minutes to fully remove oxygen in the aqueous phase, and set aside.
[0074] According to the composition of the microemulsion under the condition of the optimal HLB value of 7.5, 12.7 g of Span80 and 5.42 g of Tween80 were weighed respectively, dissolved in 51.88 g of white oil in turn using a magnetic stirrer, and after nitrogen ultrasonic deoxygenation, the mixture was transferred to a four-necked flask for standby use.
[0075] Connect the synthesis reaction device, control the speed to 600r / min, keep nitrogen flowing, add water phase to the oil phase at a rate of 1-2 drops per second at room temperature, stir and emulsify at 600r / min for 30min until the microemulsion is clear and transparent; reduce the speed to 350r / min, keep the water bath temperature constant at 40℃, add 2.25g of 5% initiator 2,2'-azo (2-methylpropyl amidine) dihydrochloride aqueous solution to the microemulsion at a rate of 1-2 drops per second. Continue the reaction for 4h to obtain an acid-resistant nano polymer microsphere emulsion.
[0076] Obtain microsphere solids. After the reaction is completed, cool and stand at room temperature; add anhydrous ethanol to perform phase change demulsification, precipitate, filter and take the precipitate, and wash with anhydrous ethanol to fully remove the oil phase adhering to the surface of the microsphere solids; place the solid in a 50°C drying oven for 24 hours to fully dry, grind, granulate, and sieve the solid microspheres to obtain acid-resistant nano-polymer microspheres with an average particle size of 175nm.
[0077] (2) Preparation of acid-resistant low molecular weight cyclodextrin polymer:
[0078] Weigh 6.75 g acrylamide, 0.75 g acrylic acid, 0.4 g allyl β-cyclodextrin, 0.6 g benzyl dithiobenzoate, 0.8 g sodium 3-(N-allyl-N-methylamino)propane-1-sulfonate and 0.1 g diallyldimethylammonium chloride, add to 15 g deionized water, and place in a 250 mL three-necked flask. Pass N 2 The solution was dissolved under stirring; the pH value of the solution was adjusted to 7 with a 20 wt% NaOH aqueous solution, and then transferred to a flask. The three-necked flask was placed in a constant temperature water bath at 40 °C and N 2 The mixture was stirred at high speed for 2 to 3 hours. Then, 4 g of 5% 2,2'-azo(2-methylpropylamidine) dihydrochloride aqueous solution was added dropwise to the system using a syringe. After stirring for 0.5 hours under nitrogen protection at room temperature, the mixture was irradiated with an ultraviolet high-pressure mercury lamp for 2 hours. A transparent colloidal product was obtained, which was cut into small pieces and purified three times with ethanol. The acid-resistant low molecular weight cyclodextrin polymer powder was obtained by crushing, vacuum drying and granulation.
[0079] (3) Preparation method of acid-resistant nano polymer microsphere inclusion plugging system:
[0080] First, weigh 0.3g of acid-resistant nano-polymer microspheres, slowly disperse them in 100mL of distilled water, and then stir at high speed for 10 minutes, so that the acid-resistant nano-polymer microspheres can be well dispersed in water without agglomeration. When the acid-resistant nano-polymer microspheres are evenly dispersed, reduce the stirring speed, put them into a 45℃ water bath at a speed of 100r / min, and expand them for 4 hours. Then stop stirring, and put the acid-resistant nano-polymer microsphere dispersion into a 45℃ constant temperature box for aging for 24 hours. Then weigh 0.3g of acid-resistant low molecular weight cyclodextrin polymer in a ratio of 1:1, and add it to the aged acid-resistant nano-polymer microsphere dispersion. Stir at a speed of 100r / min in a 45℃ water bath for 4 hours to completely dissolve the acid-resistant low molecular weight cyclodextrin polymer into the acid-resistant nano-polymer microsphere dispersion. The prepared composite system is placed in a 45℃ constant temperature box for aging for 48 hours to obtain an acid-resistant nano-polymer microsphere inclusion plugging system.
[0081] Example 2
[0082] A method for preparing an acid-resistant nano-polymer microsphere inclusion plugging system is as described in Example 1, except that: in step (1), the mass ratio of the stable cross-linking agent N,N-methylenebisacrylamide to the unstable cross-linking agent polyethylene glycol diacrylate in the acid-resistant nano-polymer microspheres is 4:1, that is, the amount of N,N-methylenebisacrylamide is 0.32g, and the amount of polyethylene glycol diacrylate is 0.08g; other steps and conditions are the same as in Example 1.
[0083] Example 3
[0084] A method for preparing an acid-resistant nano polymer microsphere inclusion plugging system is as described in Example 1, except that: the synthesis method of the acid-resistant low molecular weight cyclodextrin polymer in step (2) is a three-stage initiation method; the details are as follows:
[0085] Weigh 6.75 g acrylamide, 0.75 g acrylic acid, 0.4 g allyl β-cyclodextrin, 0.6 g benzyl dithiobenzoate, 0.8 g sodium 3-(N-allyl-N-methylamino)propane-1-sulfonate and 0.1 g diallyldimethylammonium chloride, add to 15 g deionized water, and place in a 250 mL three-necked flask. Pass N 2 The solution was dissolved under stirring; the pH value of the solution was adjusted to 7 with a 20 wt% NaOH aqueous solution, and then transferred to a flask. The three-necked flask was placed in a constant temperature water bath at 40 °C and N 2And stir at high speed for 2 to 3 hours. Then, 4g of 5% three-stage initiator aqueous solution (the mass ratio of low-temperature, medium-temperature and high-temperature initiators is 1:1:1, and the mass ratio of potassium persulfate to sodium bisulfite in the low-temperature initiator is 1:1, that is, 0.033g of potassium persulfate, 0.033g of sodium bisulfite, 0.066g of 2,2'-azo (2-methylpropyl amidine) dihydrochloride, and 0.066g of cyclohexanone peroxide) is added dropwise to the system with a syringe; stir at 5°C under nitrogen protection until the system becomes viscous, and then stand at 5°C under nitrogen protection for 6 hours. A transparent colloidal product is obtained, which is taken out and cut into small pieces, purified three times with ethanol, and then crushed, vacuum dried, and granulated to obtain an acid-resistant low molecular weight cyclodextrin polymer dry powder.
[0086] The other steps and conditions are the same as in Example 1.
[0087] Example 4
[0088] A method for preparing an acid-resistant nano-polymer microsphere inclusion plugging system is as described in Example 1, except that the mass ratio of acid-resistant nano-polymer microspheres to acid-resistant low molecular weight cyclodextrin polymer is 1:2, that is, the amount of acid-resistant nano-polymer microspheres is 0.15g, and the amount of acid-resistant cyclodextrin polymer is 0.3g; other steps and conditions are the same as in Example 1.
[0089] Example 5
[0090] A method for preparing an acid-resistant nano-polymer microsphere inclusion plugging system is as described in Example 1, except that the mass ratio of acid-resistant nano-polymer microspheres to acid-resistant low-molecular-weight cyclodextrin polymer is 2:1, that is, the amount of acid-resistant low-molecular-weight cyclodextrin polymer is 0.15g, and the amount of acid-resistant nano-polymer microspheres is 0.3g; other steps and conditions are the same as in Example 1.
[0091] Example 6
[0092] A method for preparing an acid-resistant nano polymer microsphere inclusion plugging system is as described in Example 1, except that:
[0093] In step (1), the amount of hexadecyl dimethyl allyl ammonium chloride is 0.4 g, the amount of diallyl dimethyl ammonium chloride is 0.2 g, and the modified nano-silicon dioxide (SiO 2 ) is used in an amount of 0.06g; other steps and conditions are the same as in Example 1.
[0094] Example 7
[0095] A method for preparing an acid-resistant nano polymer microsphere inclusion plugging system is as described in Example 1, except that:
[0096] In step (2), the amount of diallyldimethylammonium chloride used is 0.2 g, the amount of 3-(N-allyl-N-methylamino)propane-1-sodium sulfonate used is 0.9 g, and the amount of allyl β-cyclodextrin used is 0.5 g; other steps and conditions are the same as in Example 1.
[0097] Comparative Example 1
[0098] A method for preparing a plugging system, as described in Example 1, except that no acid-resistant cyclodextrin polymer is added; the details are as follows:
[0099] The preparation of acid-resistant nano-polymer microspheres is the same as step (1) of Example 1;
[0100] First, weigh 0.3g of acid-resistant nano-polymer microspheres, slowly disperse them in 100mL of distilled water, and then stir at high speed for 10 minutes, so that the acid-resistant nano-polymer microspheres can be well dispersed in the water without agglomerating. When the acid-resistant nano-polymer microspheres are evenly dispersed, reduce the stirring speed, put them into a 45°C water bath at a speed of 100r / min, and expand them for 4 hours. Then stop stirring, put the acid-resistant nano-polymer microsphere dispersion into a 45°C thermostat for aging for 24 hours to obtain a plugging system.
[0101] Comparative Example 2
[0102] A method for preparing a plugging system is as described in Example 1, except that the acid-resistant nano-polymer microspheres are replaced by ordinary acid-inresistant nano-polymer microspheres; that is, diallyldimethylammonium chloride is not added in step (1); and the other steps and conditions are the same as in Example 1.
[0103] Comparative Example 3
[0104] A method for preparing a plugging system is as described in Example 1, except that only a single cross-linked structure is used to prepare acid-resistant nano polymer microspheres, that is, in step (1), polyethylene glycol diacrylate is not added, and only cross-linking agent N,N-methylenebisacrylamide is used. Other steps and conditions are the same as in Example 1.
[0105] Comparative Example 4
[0106] A method for preparing a plugging system is as described in Example 1, except that: diallyldimethylammonium chloride monomer is not added in step (2); the other steps and conditions are the same as in Example 1.
[0107] Comparative Example 5
[0108] A method for preparing a plugging system is as described in Example 1, except that: in step (2), no temperature-resistant monomer 3-(N-allyl-N-methylamino) propane-1-sodium sulfonate is added; other steps and conditions are the same as in Example 1.
[0109] Comparative Example 6
[0110] A method for preparing a plugging system is as described in Example 1, except that modified nano-silicon dioxide with carbon-carbon double bonds on the surface is not added in step (1). Other steps and conditions are the same as in Example 1.
[0111] Comparative Example 7
[0112] A method for preparing a plugging system is as described in Example 1, except that no chain transfer agent is added in step (2); the other steps and conditions are the same as in Example 1.
[0113] Test Example 1
[0114] The acid resistance of the plugging system prepared in the embodiment and the comparative example was tested. The test method is as follows:
[0115] First, the volume method was used to test the expansion of polymer microspheres in water with a pH value of 4. 1.0 mL of polymer microspheres were placed in a 40 mL colorimetric tube, 30 mL of water with a pH value of 4 (aqueous solution of hydrochloric acid) was added, and the microspheres were expanded at 80°C for 24 h. The volume of the expanded polymer microspheres was recorded, and the expansion multiple of the polymer microspheres was calculated.
[0116] The viscosity of the plugging system prepared in the embodiment and the comparative example at 80°C and the plugging system in which the water is replaced with a hydrochloric acid aqueous solution with a pH value of 4 were tested using a viscometer, that is, the viscosity of the plugging system (water) and the plugging system (acid) were tested. The acid resistance of the plugging system was evaluated by the expansion multiple of the polymer microspheres and the viscosity index of the composite system.
[0117] The composite system (acid) was injected into water at a constant rate of 0.5 mL / min and the permeability was 100×10 -3 μm 2 In the core with a length of 10 cm, the actual formation shearing effect was simulated, and the viscosity of the production end system was tested. The shear retention rate was calculated by the viscosity values before and after injection to evaluate the shear resistance of the composite system (acid). The above tests were all carried out at 80°C.
[0118] The test results are shown in Table 1.
[0119] Table 1 Acid resistance of acid-resistant nano-polymer microsphere inclusion plugging system
[0120]
[0121] The results of Table 1 show that the performance of the acid-resistant nano polymer microsphere inclusion plugging system (Example 1) prepared under the optimal raw material composition and synthesis conditions is the best. Factors such as the double cross-linked structure, the ratio of acid-resistant monomers to cross-linking agents all affect the expansion performance and acid resistance of acid-resistant nano polymer microspheres; and acid-resistant monomers and temperature-resistant monomers also affect the acid resistance of acid-resistant low molecular weight cyclodextrin polymers. It can be clearly seen from the shear viscosity retention rate data that the shear resistance of almost all systems is good, and only the shear resistance of the cyclodextrin polymer composite system without chain transfer agent in Comparative Example 7 is the worst; the reason is that when the chain transfer agent is not included, the chain termination reaction of the polymer in the synthesis process is delayed, resulting in a high molecular weight and long molecular chain of the synthesized polymer. Therefore, the long-chain polymer cannot withstand the pore throat shearing effect during the migration process, resulting in the lowest system viscosity retention rate. This also reflects that the addition of chain transfer agents enables the synthesis process of cyclodextrin polymers to synthesize low molecular weight, shear-resistant polymers with better shear resistance.
[0122] Test Example 2
[0123] The CO of the plugging system prepared in the test examples and comparative examples 2 The sealing effect and enhanced oil recovery performance. The test method is as follows:
[0124] ① Saturate the core with oil and calculate the original oil saturation of the core;
[0125] ② Add a 0.03mm metal gasket in the middle of the matrix core to make a fracture core model; then place the core in the core holder, set the confining pressure to 15MPa and the back pressure to 7.6MPa;
[0126] ③Carry out CO at a constant flow rate of 0.5 mL / min 2 In the gas drive oil recovery test, the produced fluid was collected every 1 minute at the core outlet and the gas drive recovery factor was calculated;
[0127] ④ Waiting for the front CO 2 When no oil is produced at the gas drive production end, a different plugging system is injected, with the injection volume being 0.6 times the core pore volume;
[0128] ⑤ Then, CO was added at a constant flow rate of 0.5 mL / min. 2 In the subsequent gas drive, the produced fluid was collected at the core outlet every 1 minute until the core outlet stopped producing oil, and the final recovery rate was calculated. The entire oil drive and CO 2 The injection-production pressure difference changes in the plugging experiment, and the plugging rate is calculated. All the above experimental processes were operated at 80℃, and the test results are shown in Table 2.
[0129] Table 2 CO of acid-resistant nano-polymer microsphere inclusion plugging system 2 Seal performance and enhanced oil recovery effect
[0130]
[0131]
[0132] The results in Table 2 show that the acid-resistant nano-polymer microsphere inclusion plugging system prepared under the optimal conditions has a plugging rate of up to 95.23%, which has the best effect in improving the heterogeneity of the core. 2 The oil recovery enhancement effect can reach up to 16.77%. Through the data of different embodiments and comparative examples, it can be concluded that the acid-resistant monomers, double cross-linked structures, inclusion supramolecular effects and other designs introduced in the preparation scheme of polymer microspheres and polymers are successful, making the acid-resistant nano polymer microsphere inclusion plugging system have more excellent acid resistance, plugging performance and enhanced recovery effect.
[0133] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An acid-resistant nano polymer microsphere inclusion plugging system, characterized in that: The preparation method comprises the following raw materials in parts by weight: 1-5 parts of acid-resistant nano polymer microspheres, 1-5 parts of acid-resistant low molecular weight cyclodextrin polymers, and 80-120 parts of water.
2. The acid-resistant nano polymer microsphere inclusion plugging system according to claim 1, characterized in that: The acid-resistant nano polymer microsphere inclusion plugging system is prepared by including the following raw materials in parts by weight: 2-4 parts of acid-resistant nano polymer microspheres, 2-4 parts of acid-resistant low molecular weight cyclodextrin polymer, and 90-110 parts of water.
3. The acid-resistant nano polymer microsphere inclusion plugging system according to claim 1, characterized in that: The acid-resistant nano polymer microspheres are prepared from the following raw materials in parts by weight: 110-150 parts of basic building block monomers, 1-15 parts of hydrophobic monomers, 1-20 parts of acid-resistant monomers, 0.1-3 parts of nano particles, 0.3-6 parts of double cross-linking agent system, 0.2-3 parts of initiator, 150-200 parts of emulsifier, 500-550 parts of oil phase solvent, and 100-200 parts of water; Preferably, the acid-resistant nano polymer microspheres are prepared by including the following raw materials in parts by weight: 130-140 parts of basic building block monomers, 2-4 parts of hydrophobic monomers, 1-2 parts of acid-resistant monomers, 0.4-0.6 parts of nanoparticles, 3-5 parts of double cross-linking agent systems, 0.8-1.2 parts of initiators, 180-185 parts of emulsifiers, 510-520 parts of oil phase solvents, and 155-160 parts of water.
4. The acid-resistant nano polymer microsphere inclusion plugging system according to claim 3, characterized in that: Includes one or more of the following conditions: i. The basic building block monomer is acrylamide (AM); ii. The hydrophobic monomer is hexadecyl dimethyl allyl ammonium chloride; iii. The acid-resistant monomer is diallyldimethylammonium chloride; iv. The nanoparticles are modified nano-silicon dioxide (SiO2) with carbon-carbon double bonds on the surface, the modified nano-silicon dioxide (SiO2) has the structure shown below, and the particle size is 1-10 nm; v. The dual crosslinker system is a combination of a stable crosslinker N,N-methylenebisacrylamide and an unstable crosslinker polyethylene glycol diacrylate, wherein the mass ratio of N,N-methylenebisacrylamide to polyethylene glycol diacrylate is 6:4-9:1, preferably 2:1-4:1; vi. The initiator is 2,2'-azo(2-methylpropylamidine) dihydrochloride; vii. The emulsifier is a combination of sorbitan fatty acid ester and polyoxyethylene sorbitan monooleate, wherein the mass ratio of sorbitan fatty acid ester to polyoxyethylene sorbitan monooleate is 2-3:1; viii. The oil phase solvent is white oil.
5. The acid-resistant nano polymer microsphere inclusion plugging system according to claim 3, characterized in that: The method for preparing acid-resistant nano polymer microspheres comprises the following steps: (1) fully dispersing the basic building block monomer, the hydrophobic monomer, the acid-resistant monomer, the nanoparticles, and the dual crosslinking agent system in water to obtain an aqueous phase; (2) dissolving an emulsifier in an oil phase solvent to obtain an oil phase; (3) mixing the aqueous phase and the oil phase and emulsifying them to obtain a microemulsion; (4) adding an initiator aqueous solution dropwise to the microemulsion, reacting, then breaking the emulsion by phase transition, filtering, washing, drying, grinding, granulating, and sieving to obtain acid-resistant nano polymer microspheres; Preferably, in step (3), the aqueous phase is added dropwise to the oil phase at a rate of 1-2 drops per second at room temperature and 500-700 r / min stirring; Preferably, in step (3), the emulsification speed is 500-700 r / min, and the emulsification time is 20-40 min; Preferably, in step (4), the mass concentration of the initiator aqueous solution is 1%-5%; the dropping rate is 1-2 drops per second; the dropping temperature is 35-50°C; the dropping is carried out under stirring at 300-400r / min and protective gas protection conditions; preferably, the protective gas is nitrogen or argon; Preferably, in step (4), the reaction temperature is 35-50° C., the reaction time is 3-6 hours, and the reaction is carried out at a stirring rate of 300-400 r / min and under the protection of a protective gas; preferably, the protective gas is nitrogen or argon.
6. The acid-resistant nano polymer microsphere inclusion plugging system according to claim 1, characterized in that: The acid-resistant low molecular weight cyclodextrin polymer is prepared by the following raw materials in parts by weight: 60-80 parts of basic building unit monomer a, 1-10 parts of inclusion monomer, 1-5 parts of acid-resistant monomer a, 1-10 parts of temperature-resistant monomer a, 1-10 parts of raft chain transfer agent, 2-4 parts of initiator system, and 100-200 parts of water; Preferably, the acid-resistant low molecular weight cyclodextrin polymer is prepared by the following raw materials in parts by weight: 70-80 parts of basic building unit monomer a, 3-5 parts of inclusion monomer, 1-2 parts of acid-resistant monomer a, 7-9 parts of temperature-resistant monomer a, 5-7 parts of raft chain transfer agent, 1-3 parts of initiator system, and 140-160 parts of water.
7. The acid-resistant nano polymer microsphere inclusion plugging system according to claim 6, characterized in that: Includes one or more of the following conditions: i. The basic building block monomer a is a combination of acrylamide (AM) and acrylic acid (AA), wherein the mass ratio of acrylamide (AM) to acrylic acid (AA) is 8:1-10:1; ii. The inclusion monomer is allyl β-cyclodextrin; iii. Acid-resistant monomer a is diallyldimethylammonium chloride; iv. The heat-resistant monomer a is sodium 3-(N-allyl-N-methylamino) propane-1-sulfonate; v. Raft chain transfer agent is benzyl dithiobenzoate; vi. The initiator system is a three-stage initiator or a photoinitiator; preferably, the three-stage initiator system is a combination of a low-temperature initiator, a medium-temperature initiator and a high-temperature initiator; the low-temperature initiator is potassium persulfate and sodium bisulfite, and the mass ratio of potassium persulfate to sodium bisulfite is 1:1; the medium-temperature initiator is 2,2'-azo (2-methylpropyl amidine) dihydrochloride; the high-temperature initiator is cyclohexanone peroxide; the mass ratio of the low-temperature initiator, the medium-temperature initiator and the high-temperature initiator is 1:1:1; the photoinitiator is a water-soluble photoinitiator 2,2'-azo (2-methylpropyl amidine) dihydrochloride.
8. The acid-resistant nano polymer microsphere inclusion plugging system according to claim 6, characterized in that: The method for preparing an acid-resistant low molecular weight cyclodextrin polymer comprises the following steps: The basic building unit monomer a, the inclusion monomer, the acid-resistant monomer a, the heat-resistant monomer a, and the raft chain transfer agent are fully dispersed in water, and the pH of the system is adjusted to 7; the initiator system is added dropwise, reacted, and then washed, crushed, dried, and granulated to obtain an acid-resistant low molecular weight cyclodextrin polymer; Preferably, a NaOH aqueous solution with a mass concentration of 10-30% is used to adjust the pH of the system; Preferably, when the initiator system is a three-stage initiator, the initiator system is an aqueous solution of the three-stage initiator with a mass concentration of 2%-5%; the reaction conditions are as follows: stirring at 3-8°C under protective gas protection until the system becomes viscous, and then standing at 3-8°C under protective gas protection for 1-10 hours; further preferably, the protective gas is nitrogen or argon; Preferably, when the initiator system is a photoinitiator, the reaction is carried out under ultraviolet light irradiation and protective gas protection, the reaction temperature is room temperature, and the reaction time is 2-4 hours; further preferably, the protective gas is nitrogen or argon; the ultraviolet light is provided by an ultraviolet high-pressure mercury lamp.
9. The method for preparing the acid-resistant nano polymer microsphere inclusion plugging system according to any one of claims 1 to 8, comprising the steps of: The acid-resistant nano polymer microspheres are fully dispersed in water, expanded and aged to obtain a microsphere dispersion; an acid-resistant low molecular weight cyclodextrin polymer is added, fully dispersed, and then aged to obtain an acid-resistant nano polymer microsphere inclusion plugging system; Preferably, the expansion reaction temperature is 40-50°C, the expansion reaction time is 2-6h, and the expansion reaction is carried out under stirring conditions of 50-200r / min; Preferably, during the preparation of the microsphere dispersion, the aging reaction temperature is 40-50°C and the aging reaction time is 20-30h; Preferably, after adding the acid-resistant low molecular weight cyclodextrin polymer, stirring is performed at 40-50° C. and 50-200 r / min for 2-6 hours to fully disperse; Preferably, after adding the acid-resistant low molecular weight cyclodextrin polymer, the aging reaction temperature is 40-50° C., and the aging reaction time is 30-70 hours.
10. The use of the acid-resistant nano polymer microsphere inclusion plugging system according to any one of claims 1 to 8, characterized in that: Used to block gas channel in CO2 flooding reservoirs.
Citation Information
Patent Citations
Pre-crosslinking gel retarding-swelling microsphere profile control agent and preparation method and application thereof
CN106883357A
Polymer microsphere as well as preparation method and application thereof
CN111793164A
Synergistic supramolecular inclusion polymer oil displacement system as well as preparation method and application thereof
CN117946652A
High-temperature-resistant profile control plugging agent and preparation method thereof
CN118005854A
Self-assembly profile control and displacement system and preparation method thereof
CN118240537A
Cited By
Temperature-sensitive supramolecular host-guest inclusion in-situ synergistic oil displacement system as well as preparation method and application thereof
CN121136694A